2010
DOI: 10.1128/aem.00221-10
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Microbial Communities Colonizing Leaf Litter in a Temperate Woodland Stream by Growth of Trees under Conditions of Elevated Atmospheric CO 2

Abstract: Elevated atmospheric CO 2 can cause increased carbon fixation and altered foliar chemical composition in a variety of plants, which has the potential to impact forested headwater streams because they are detritusbased ecosystems that rely on leaf litter as their primary source of organic carbon. Fungi and bacteria play key roles in the entry of terrestrial carbon into aquatic food webs, as they decompose leaf litter and serve as a source of nutrition for invertebrate consumers. This study tested the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…The most common fungal identity was the uncultured fungus clone AA45‐20 (33% of all OTUs), which has been reported in only a single study in a woodland stream in North America (Kelly et al . ) (these strains were 100% similar by the sequenced region). The proportional abundance of the uncultured fungus clone AA45‐20 correlated strongly with fungal evenness ( r = −0.…”
Section: Resultsmentioning
confidence: 87%
“…The most common fungal identity was the uncultured fungus clone AA45‐20 (33% of all OTUs), which has been reported in only a single study in a woodland stream in North America (Kelly et al . ) (these strains were 100% similar by the sequenced region). The proportional abundance of the uncultured fungus clone AA45‐20 correlated strongly with fungal evenness ( r = −0.…”
Section: Resultsmentioning
confidence: 87%
“…A recent study also found that fungal communities were not affected by litter quality changes induced by increased atmospheric CO 2 (Kelly et al 2010). However, when differences in litter quality are greater, for example, between litter species, aquatic hyphomycete community structure can be affected (Gulis 2001;Ferreira et al 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Litter toughness has been shown to determine litter decomposition rates, sometimes even overcoming the importance of litter chemistry (Quinn et al 2000;Li et al 2009). The few studies addressing the effects of changes on litter quality induced by increases in atmospheric CO 2, on aquatic microbial communities and litter decomposition have shown that these effects are stronger at early stages of litter decomposition than at later stages, when secondary compounds have been leached; however, overall they remain weak and speciesdependent (Rier et al , 2005Tuchman et al 2003b;Kelly et al 2010). Evidence from terrestrial systems also indicates that the effects of elevated CO 2 on litter quality are species specific and not always translated into differences in litter decomposition rates (Gorissen and Cotrufo 2000;King et al 2001;Norby et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial phylotype richness increased with reduced community‐weighted means of leaf C/N (Table ; Table S4). Generally, leaves with higher C/N ratios are decomposed more slowly than those with a low C/N ratio, likely due to reduced nitrogen availability and, consequently, lower bacterial diversification (Kelly et al., ) or the promotion of resource partitioning among the component soil organisms (Wardle, ). In line with finding, leaf C/N was significantly positively correlated with the relative abundance of Acidobacteria , which can adapt to low nutrient availability (Table S6).…”
Section: Discussionmentioning
confidence: 99%